SOME DEVELOPMENT FOR NEWTON'S METHOD UNDER MILD DIFFERENTIABILITY CONDITIONS - Argyros, I.K.; Khattri, S.K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2014)
We develop a semilocal convergence analysis for Newton's method under mild differentiability conditions. Our sufficient convergence conditions can be weaker than conditions found in earlier studies such as [11-14,16,18-21]. Numerical examples are also provided.